DETERMINANT OF IMPLEMENTATION PROFIT SHARING FINANCING IN ISLAMIC BANKING - Winarsih, Winarsih; Asokawati, Winda (UNISSULA, 2019)
One of the characteristics of Islamic banking is using the concept of profit sharing financing. This study aims to determinan of implementation profit sharing financing, consist of Third Party Funds , Non Performing Financing, Return On Assets, Capital Adequacy Ratio and Financing to Deposit Ratio. The population in this study are all Islamic banking which listed in Bank of Indonesia in the periode 2013 to 2016. The sample was selected using purposive sampling methodTotal samples used in this study were 11 Islamic Banks with 4-year study period, with get sampleof 44 data. The analytical method used in this study is multiple regression were processed using SPSS. The results of this study indicate third party funds, financing to deposit ratio have a positive significant effect to the financing profit sharing. While non performing financing ,return on asset and capital adequacy ratio no effect on the profit sharing financing.